2D Re‐Based Transition Metal Chalcogenides: Progress, Challenges, and Opportunities. Issue 23 (25th October 2020) - Li, Xiaobo; Chen, Chao; Yang, Yang; Lei, Zhibin; Xu, Hua
Abstract: The rise of 2D transition‐metal dichalcogenides (TMDs) materials has enormous implications for the scientific community and beyond. Among TMDs, ReX2 (X = S, Se) has attracted significant interest regarding its unusual 1T′ structure and extraordinary properties in various fields during the past 7 years. For instance, ReX2 possesses large bandgaps (ReSe2 : 1.3 eV, ReS2 : 1.6 eV), distinctive interlayer decoupling, and strong anisotropic properties, which endow more degree of freedom for constructing novel optoelectronic, logic circuit, and sensor devices. Moreover, facile ion intercalation, abundant active sites, together with stable 1T′ structure enable them great perspective to fabricate high‐performance catalysts and advanced energy storage devices. In this review, the structural features, fundamental physicochemical properties, as well as all existing applications of Re‐based TMDs materials are comprehensively introduced. Especially, the emerging synthesis strategies are critically analyzed and pay particular attention is paid to its growth mechanism with probing the assembly process of domain architectures. Finally, current challenges and future opportunities regarding the controlled preparation methods, property, and application exploration of Re‐based TMDs are discussed. Abstract : A review of 2D Re‐based transition metal chalcogenides (TMDs) is presented to introduce their crystal and electronic band structures, and to highlight the recent progress on fabrications, properties, and applications. In addition, the current challenges and future opportunities of ReX2 are discussed. This review provides a comprehensive summary about Re‐based TMDs, and sheds light on the current direction of research in this field.